The Effect of the Quizizz Assisted Teams Games Tournament (TGT) Model on Fourth Grade Elementary School Students’ Learning Interest in the Effects of Force on Objects - Ali Ahmad; Septi Fitri Meilana (FKIP - Universitas Riau, 2026)
Learning interest is important in encouraging elementary school students to participate actively in learning. However, IPAS learning on the effects of force on objects may still be dominated by teacher-centered activities, resulting in limited student involvement. This study aimed to examine the effect of the Quizizz assisted Teams Games Tournament (TGT) on fourth grade students’ learning interest. A quantitative approach with a quasi-experimental method and Static Group Comparison Design was used. The study involved 60 fourth grade students, with 30 students in the experimental group receiving Quizizz assisted TGT and 30 students in the control group receiving Quizizz assisted Student Teams Achievement Division (STAD). Data were collected using a learning interest questionnaire consisting of 16 valid items with a Cronbach’s Alpha coefficient of 0.831. Data analysis involved normality, homogeneity, and Independent Samples t test. The results showed a significant difference in learning interest between the two groups (t = 5.639, df = 58, p = 0.001), with the experimental group achieving a higher mean score than the control group. Thus, Quizizz assisted TGT significantly affected students’ learning interest in learning about the effects of force on objects.